Yoga: As an adjunct therapy to trim down the Ayurvedic drug requirement in non insulin-dependent diabetes mellitus - Rohit Sharma (Ancient Science of Life, 2014)
Introduction: In spite of a large number of drugs showing anti-hyperglycemic activities, none of them have been successful in complete management of diabetes mellitus (DM). Yoga and Ayurveda are the two schools of thought in India, which have a history of curing diseases since thousands of years. Yogic techniques and Ayurvedic herbs have proven their anti-diabetic potential without inducing untoward effects. The present study combines Ayurvedic medication with Yoga techniques as a new approach toward healing DM. Aims and Objectives: To assess the effect of Yoga therapy in the management of non insulin-dependent DM (NIDDM) and to decrease the oral drug dose requirement of guḍŪcī ghana Tablet. Materials and Methods: Thirty known NIDDM patients of both genders, who were on guḍŪcī ghana (solidified aqueous extract of Tinospora cordifolia (Willd.) Miers.) tablets from past 2 months as Ayurvedic remedy for DM were selected. Along with guḍŪcī ghana administration, the subjects were instructed to follow Yogic procedures including Āsanas , prāṇāyāma, and śuddhi kriyās . The study was conducted for 8 weeks, wherein fasting blood sugar (FBS) and postprandial blood sugar (PPBS) levels along with relief in sign and symptoms were assessed at every 2 weeks intervals, and according to relief in sign and symptoms, tapering of drug dosage was carried out. The obtained data were analyzed statistically by applying paired t-test. Results and Conclusion: The results obtained were promising as the relief in diabetic symptomatology was highly significant in terms of P value. 80.83% reduction in dose of guḍŪcī ghana tablets and 7.85% and 8.78% fall in FBS and PPBS levels, respectively, after the complete course of treatment. The obtained P value showed highly significant results.